The Role of ESG Criteria in Reaching Sustainable Development in Germany - Hrdina, Jakub (2025)
This thesis explores the role of Environmental, Social, and Governance (ESG) criteria in reaching sustainable development in Germany, with a specific focus on the implementation of EU sustainability legislation. Using a comparative study approach, the research analyzes the ESG-related policies of two German federal governments—those of Angela Merkel (2018–2021) and Olaf Scholz (2021–2025). The thesis examines how ESG principles were incorporated into political programs and actual policy decisions, and to what extent they aligned with EU frameworks such as the European Green Deal, Fit for 55, and the Corporate Sustainability Reporting Directive. Content analysis of party platforms, legislative documents, and empirical indicators shows that successful ESG integration depends on political coherence, institutional capacity, and economic flexibility. The study contributes to the ongoing debate about the effectiveness of ESG as a tool for real-world sustainability transitions at the national level.